1996
DOI: 10.1021/ma9513630
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Mechanical Study of Sodium Sulfonated Random Ionomers Based on Hydrogenated Styrene−Butadiene Copolymer

Abstract: Sodium sulfonated poly(styrene-ethylene-butylene) random ionomers [P(SEB-co-SSNa)] were obtained by hydrogenation, sulfonation, and neutralization of styrene-butadiene copolymers containing 45 wt % styrene. The dynamic mechanical properties were measured as a function of temperature for ionomers of a wide range of ion contents. Most of the ionomers showed two glass transitions, as well as a well-developed ionic plateau region in the storage modulus between the two glass transitions. The loss tangent peak of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…7 mol%; above 10 mol% of ions, the volume fraction of the cluster regions does not change significantly with ion content. 8 From this, along with morphological data above, it can be concluded that when clustering is well-developed, scattering centers are also fully developed, and thus Bragg distance does not change significantly with ion content. Similar observations have also been made in the poly(styrene-co-methacrylate) ionomer system.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…7 mol%; above 10 mol% of ions, the volume fraction of the cluster regions does not change significantly with ion content. 8 From this, along with morphological data above, it can be concluded that when clustering is well-developed, scattering centers are also fully developed, and thus Bragg distance does not change significantly with ion content. Similar observations have also been made in the poly(styrene-co-methacrylate) ionomer system.…”
Section: Resultsmentioning
confidence: 59%
“…8 The PSEB copolymer is composed of 73 mol% of ethylene, 8 mol% of butylene, and 19 mol% of styrene. The polymer was sulfonated using a modification of the sulfonation method of Thaler.…”
Section: Polymer Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[54] Nishida et al investigated the dynamic mechanical properties of randomly sodium sulfonated poly(styrene-ethylene-butylene) ionomers and the filler concept was used to explain the increase in the storage modulus in the ionic plateau region. [55] The tan d curves for PBSis showed two T g , Figure 3(b). The main peak was assigned as the T g of the matrix, while the shoulder at a higher temperature reflected the T g corresponding to the ion cluster region.…”
Section: Physical Properties Of Aliphatic Polyester-based Ionomersmentioning
confidence: 97%
“…Fitzgerald and Weiss [12] studied the effect of glycerol and dioctyl phthalate on the dynamic mechanical properties of sulfonated polystyrene using a dynamic mechanical analyzer and smallangle X-ray scattering. Nishida and Eisenberg [13] studied the dynamic mechanical properties of sulfonated ionomer of hydrogenated (styrene-butadiene) rubber neutralized with sodium ions and indicated that most of the ionomers showed two glass transitions, as well as a well-developed ionic plateau region in the storage modulus between the two glass transitions. Nishida and Eisenberg [13] studied the dynamic mechanical properties of sulfonated ionomer of hydrogenated (styrene-butadiene) rubber neutralized with sodium ions and indicated that most of the ionomers showed two glass transitions, as well as a well-developed ionic plateau region in the storage modulus between the two glass transitions.…”
Section: Introductionmentioning
confidence: 99%